2018
DOI: 10.1111/ppa.12832
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative resistance against an isolate of Leptosphaeria maculans (blackleg) in selected Canadian canola cultivars remains effective under increased temperatures

Abstract: Blackleg disease, caused by Leptosphaeria maculans, is a serious threat to canola production in western Canada. While specific major resistance (R) genes can be effective, they can also be eroded rapidly by a shift in pathogen race composition. Quantitative resistance (QR) has the potential to provide more durable, if less complete, protection. However, the effectiveness of QR may vary widely in the field. It has long been suspected that elevated temperatures may limit the expression of QR. To test this hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Specifically, more restricted host tissue colonization and lesion development were observed on 74-44 BL, relative to Westar. Earlier studies [12,32] also found consistent QR with 74-44 BL in stems, as well as in cotyledons, against multiple Lm races, confirming the race-nonspecific nature of resistance. This study also found that the Lm hyphal growth often extended beyond the borders of visible lesions in Westar, while the growth was consistently restricted within the lesion in 74-44 BL.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Specifically, more restricted host tissue colonization and lesion development were observed on 74-44 BL, relative to Westar. Earlier studies [12,32] also found consistent QR with 74-44 BL in stems, as well as in cotyledons, against multiple Lm races, confirming the race-nonspecific nature of resistance. This study also found that the Lm hyphal growth often extended beyond the borders of visible lesions in Westar, while the growth was consistently restricted within the lesion in 74-44 BL.…”
Section: Discussionsupporting
confidence: 68%
“…However, the enrichment analysis did not uncover any GO terms related to PCD (Supplementary Tables S6 and S7). Furthermore, the upregulation of BnaC09g20030D, with sequence similarity to a Bax inhibitor-1, might negate the effect of BnaCnng58090D by inhibiting PCD [32]. The hypersensitivity that DCD would otherwise be induced in response to infection might be prevented by the upregulation of BnaC09g20030D in Westar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent data showed lower presence of AvrLm1 in L . maculans populations 28,29 due to use of Rlm1 in canola cultivars extensively 30 , Rlm1 could still be valuable for effective control of blackleg disease in Canada as a strategy through rotation of R genes that has been recently implemented.…”
Section: Introductionmentioning
confidence: 99%
“…have been identified [29,30,31,32,33]. Apart from the qualitative resistance (major gene resistance), the effect of quantitative resistance against an isolate of L. maculans in selected Canadian canola cultivars under increased temperature was investigated [34]. Very few studies have reported on the effects of environmental changes, especially the CO 2 concentration, on the interactions of the B. napus–L.…”
Section: Introductionmentioning
confidence: 99%